Pemberian Ekstrak Rimpang Kunyit Putih Terhadap Efek Fertilitas Pada Testis - Nicolas Xavier Ongko; Ginting, Sahna Ferdinand (Jurnal Maternitas Kebidanan, 2024)
Traditional medicine is an alternative in medicine because of the minimal side effects and low cost. One of the spices that are widely grown in Indonesia and used for traditional medicine is white turmeric rhizome. White turmeric rhizome has a chemical content such as curcumin which can be used as an anticancer. The function of white turmeric rhizome as an anticancer is not selective and may interfere with the normal cell function that actively performs mutation such as seminiferous tubule cells can cause antifertility effect. This study aims to find out the antifertility effects of white turmeric rhizomes in the testis. This paper uses a literature review by searching through PubMed for the last 10 year studies published between 2014-2024. Based on the results of the literature study, it can be concluded that there was an antifertility effect of white turmeric rhizome.